A study of snow drifting on a flat roof during snowfall based on simulations in a cryogenic wind tunnel. Issue 188 (May 2019) - Qiang, Shengguan; Zhou, Xuanyi; Kosugi, Kenji; Gu, Ming
Abstract: Wind tunnel simulation is a very important approach to studying snow drifting and predicting drift snow loads on roofs. A complete simulation of the full process of wind-induced snow accumulation on a roof should include snow drifting both during snowfall and after snowfall. However, in most of the previous studies, snow drifting phenomenon was only simulated without concurrence of snowfall. We herein describe simulations of snow drifting on a flat roof during snowfall, which were carried out in a cryogenic wind tunnel using artificial snow particles. Based on the results, we demonstrate the differences and similarities between snow drifting during snowfall and that without concurrent snowfall. The developments of snow transport before saturated state apparently follow the same rule, no matter whether there is concurrent snowfall or not. However, it seems that the required fetch distance for a saturated saltation state can be reduced by snowfall. A formula is proposed to more reasonably describe the development of snow transport rate. Based on test results and deductions, some discussions on similarity requirements for modelling snow drifting on roofs during snowfall will be presented. Finally, a prediction of the prototype fetch distances under different wind and snowfall conditions will also be presented, which can provide a guide for further research and engineering application. Highlights: Wind tunnel tests of snow drifting during snowfall are described. Drifting development during snowfall follows the same rule as that without snowfall. Snowfall may reduce the required fetch distance for a saturated state of drifting. Similarity requirements for simulating snowfall are discussed and proposed.